Antioxidant activity and protective effect of phyto‐active compounds of Crataegus azarolus berries decoction extract against acetic acid‐induced hepatorenal injuries in male rats - Houcem Sammari; Anouar Abidi; Saber Jedidi; Nourhen Dhawefi; Hichem Sebai (Physiological Reports)
Abstract The present study evaluated the hepato‐nephronal protective properties of Crataegus azarolus berries decoction extract (CAB‐DE) on acetic acid (AA)‐induced oxidative stress and metabolic disorders in rats. Animals (60 rats) were randomly divided into six groups (n = 10), with groups 1 and 2 being controls and groups 3, 4, and 5 given increasing doses of CAB‐DE, group 6 were given gallic acid until ulcerative colitis was induced and then intoxicated by an acute intra‐rectal infusion of AA. Our results showed that CAB‐DE‐oral administration had no signs of toxicity or abnormal behavior in rats, with a LD50 higher than 3500 mg/kg bw. In addition, CAB‐DE protected against AA‐induced nephropathy and hepatic damage in rats, as determined by an increase in organ weights and an alteration in the renal and liver parameters and functions. Moreover, extract co‐administration reduced AA‐induced liver and kidney lipoperoxidation, maintained non‐enzymatic contents such as sulfhydryl groups (‐SH) and reduced glutathione (GSH), and restored antioxidant enzyme activities, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). Finally, CAB‐DE might have a possible protective effect against AA‐oxidative stress and dysfunction in the rat liver and kidney, suggesting that Crataegus azarolus berries may be beneficial for people suffering from liver issues and nephropathy.